2009
DOI: 10.1038/nn.2410
|View full text |Cite
|
Sign up to set email alerts
|

The oligodendrocyte-specific G protein–coupled receptor GPR17 is a cell-intrinsic timer of myelination

Abstract: The bHLH transcription factor Olig1 promotes oligodendrocyte maturation and is required for myelin repair. In this report, we characterize an Olig1-regulated G-protein coupled receptor GPR17 whose function is to oppose the action of Olig1. GPR17 is restricted to oligodendrocyte lineage cells but downregulated during the peak period of myelination and in adulthood. Transgenic mice with sustained GPR17 expression in oligodendrocytes exhibit stereotypic features of myelinating disorders in the CNS. GPR17 overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
374
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(401 citation statements)
references
References 50 publications
25
374
2
Order By: Relevance
“…Gpr17-knockout mice show early-onset oligodendrocyte myelination, while Gpr17 overexpression inhibits oligodendrocyte differentiation and maturation both in vivo and in vitro [26] . However, another study showed that treatment with the endogenous GPR17 ligand UDP-glucose promotes the differentiation of oPCs into mature myelin basic protein-positive oligodendrocytes [30] .…”
Section: G Protein-coupled Receptor 17mentioning
confidence: 98%
See 1 more Smart Citation
“…Gpr17-knockout mice show early-onset oligodendrocyte myelination, while Gpr17 overexpression inhibits oligodendrocyte differentiation and maturation both in vivo and in vitro [26] . However, another study showed that treatment with the endogenous GPR17 ligand UDP-glucose promotes the differentiation of oPCs into mature myelin basic protein-positive oligodendrocytes [30] .…”
Section: G Protein-coupled Receptor 17mentioning
confidence: 98%
“…olig2 induces transcription factors that are required for the generation of mature, postmitotic oligodendrocytes, notably olig1, Sox-10, Nkx2.2, Nkx6.2, Ying Yang 1, and ZFP488 [18][19][20][21][22][23] . in counterbalance, transcription [24][25][26] .…”
Section: Intrinsic Signalsmentioning
confidence: 99%
“…Activated OPCs proliferate, migrate and rapidly fill up the demyelinated lesions at a density that far exceeds that in normal tissue. To complete the remyelination process, the cells exit the cell cycle and differentiate into myelin sheath-forming oligodendrocytes, which is a complex process involving axon engagement, ensheathment and formation of compacted myelin [30,31]. As with all regenerative processes the efficiency of remyelination decreases with age primarily due to a decrease in the ability of recruited cells to differentiate [32][33][34][35].…”
Section: Remyelination As Regenerative Therapymentioning
confidence: 99%
“…In the intact brain and spinal cord, GPR17 is specifically expressed by a subset of early bipolar NG2 positive (GPR17 + ‐NG2 + ) OPCs, accompanies OPC maturation up to immature/pre‐oligodendrocytes and is then downregulated before terminal maturation (Lecca et al, 2008; Ceruti et al, 2009). Any alterations in this precise expression pattern result in myelination defects (Chen et al, 2009; Fumagalli et al, 2011; Fumagalli et al, 2015). Pathologically increased levels of GPR17 have been found after focal lysolecithin induced demyelination (Boda et al, 2011), following brain ischemia in rodents subjected to middle cerebral artery occlusion (MCAO) (Ciana et al, 2006; Lecca et al, 2008) and after traumatic brain injury in both rodents (Boda et al, 2011) and human subjects (Franke et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Pathologically increased levels of GPR17 have been found after focal lysolecithin induced demyelination (Boda et al, 2011), following brain ischemia in rodents subjected to middle cerebral artery occlusion (MCAO) (Ciana et al, 2006; Lecca et al, 2008) and after traumatic brain injury in both rodents (Boda et al, 2011) and human subjects (Franke et al, 2013). In initial studies, the mRNA for GPR17 was also found to be increased in the spinal cord of mice with experimental autoimmune encephalomyelitis (EAE) and in the spinal lesions of multiple sclerosis patients (Chen et al, 2009). The exact significance of persistent GPR17 overexpression in vivo under demyelinating conditions is still unknown.…”
Section: Introductionmentioning
confidence: 99%